CALCULATION OF 6Li -INTERACTION POTENTIAL IN THE CLUSTER FOLDING-MODEL - Burkova, N.A.; Zhusupov, M.A.; Kabatayeva, R.S. (Recent Contributions to Physics, 2017)
In the present article the results of analitical and numerical calculations of a6Li-interaction potential in the cluster folding-model are represented, when the target-nucleus has the cluster 6Liad structure.